2014
DOI: 10.1103/physreva.89.032706
|View full text |Cite
|
Sign up to set email alerts
|

Energy-loss contribution to grazing scattering of fast He atoms from a silver surface

Abstract: The energy lost by helium atoms axially scattered from a Ag(110) surface is studied in order to investigate the influence of dissipative processes on fast atom diffraction spectra. In this work inelastic projectile distributions are evaluated within a semiclassical formalism that includes dissipative effects due to electron-hole excitations through a friction force. For incidence along the [112] and [110] directions the model predicts the presence of multiple peaks in the energy-loss spectrum for a given impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…In this work we extend a previous study [32] to investigate the energy lost by 3 He atoms grazingly colliding with Ag(110) along the [1 10], [1 12] and [001] channels. Impact energies E i ranging from 0.5 keV to 2 keV and perpendicular energies E i⊥ = E i sin 2 θ i varying from 0.15 eV to 0.87 eV are considered, θ i being the incidence angle measured with respect to the surface plane.…”
Section: Resultsmentioning
confidence: 92%
“…In this work we extend a previous study [32] to investigate the energy lost by 3 He atoms grazingly colliding with Ag(110) along the [1 10], [1 12] and [001] channels. Impact energies E i ranging from 0.5 keV to 2 keV and perpendicular energies E i⊥ = E i sin 2 θ i varying from 0.15 eV to 0.87 eV are considered, θ i being the incidence angle measured with respect to the surface plane.…”
Section: Resultsmentioning
confidence: 92%
“…All these tools are based on the Born-Oppenheimer approximation (BOA), where the PESs can be computed using pairwise-like analytical functions 18,19,30,39,[45][46][47][48] or density functional theory (DFT). 21,25,26,33,[49][50][51][52][53][54][55] PESs computed at multiconfiguration self-consistent field level, considering a cluster model, have also been used. 1,17 To perform the dynamics calculations, several approaches have been adopted, from classical 49,51,52 to quantum 1,12,17,26,30,47,55 methods, as well as semiclassical 28,36,41,56 and semi-quantum 18,21,25,50,53,[57][58][59] methods.…”
Section: Introductionmentioning
confidence: 99%
“…In the last time grazing-incidence fast atom diffraction (GIFAD or FAD) [1,2] has emerged as a powerful surface analysis technique that allows one to inspect ordered surfaces, providing detailed information on their morphological and electronic characteristics [3][4][5]. The extreme sensitivity of FAD patterns to the projectile-surface interaction relies on the preservation of quantum coherence [6][7][8][9], and in this aspect the collimating conditions of the incident beam play an important role. In particular, recent experimental [10] and theoretical [11] works have shown that FAD patterns are strongly affected by the width of the collimating aperture, which determines that two different mechanisms -Bragg diffraction or supernumerary rainbows -can be alternatively observed.…”
Section: Introductionmentioning
confidence: 99%